FLUID MECHANICS FOR CHEMICAL ENGINEERS - De Nevers, Noel; Silcox, G. D. (Geoffrey Damian) (McGraw-Hill Education, 2021)
The 4th edition of Fluid Mechanics for Chemical Engineers retains the qualities that have made earlier editions popular. It is readable, accessible, and filled with intriguing examples and problems that bring the material to life. Many of the examples are based on household items that students can observe every day. Some of the new material that has been added includes wind turbines, hydraulic fracturing, and microfluidics.